Suksesi Pendidikan Nasional (Analisis Intervensi Politik Pemerintah Provinsi) - Asril Umar; Muhammad Sirozi; Solihah Titin Sumanti (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Efforts to improve the quality of national education have become a primary agenda for the Indonesian government. However, the implementation of educational policies in Indonesia is not without challenges and dynamics, including political intervention. This study aims to analyze the political intervention of provincial governments in the success of national education in Indonesia. The main focus of this research is to evaluate the extent to which such political interventions affect the quality and equity of education. This study employs a qualitative approach using case study methods in several provinces in Indonesia. Data were collected through in-depth interviews with education stakeholders, policy document analysis, and field observations. The results indicate that political intervention significantly impacts the implementation of educational policies in terms of budgeting, resource distribution, and program execution. However, political intervention is also found to often create conflicts of interest that can hinder the achievement of national education goals. This study concludes that to achieve better educational success, more transparent and accountable policies are needed, as well as strengthened coordination between the central and provincial governments. With strong commitment and appropriate policies, such interventions can bring significant positive changes to the education system, thereby producing a competitive generation ready to face future challenges.